Identifying priority areas for surface water protection in data scarce regions: An integrated spatial analysis for Zambia. Issue 8 (26th May 2021) - Lehner, Bernhard; Katiyo, Loreen; Chivava, Faith; Sichingabula, Henry M.; Nyirenda, Edwin; Rivers‐Moore, Nicholas A.; Paxton, Bruce R.; Grill, Günther; Nyoni, Frank; Shamboko‐Mbale, Beauty; Banda, Kawawa; Thieme, Michele L.; et al.
Abstract: This study aimed to develop an integrated analytical framework to identify candidate sites for surface water protection that is applicable at broad scales and in data scarce regions, using Zambia as a case study. In the Zambian Water Resources Management Act of 2011, Water Resource Protection Areas are defined as areas where special measures are necessary for the protection of a catchment, sub‐catchment, aquifer, or geographical area. Three specific selection criteria are listed for the definition of Water Resource Protection Areas: (i) areas of high importance in providing water to users in a catchment; (ii) aquatic areas of high ecological importance; and (iii) areas that are particularly sensitive to human impact. In this project, each sub‐catchment and river reach of Zambia was characterized for their importance regarding these three criteria. 'Water provisioning' was assessed by analysing patterns of runoff generation and human water use; 'aquatic ecological importance' was determined by conducting a freshwater biodiversity and ecosystem assessment using a systematic conservation planning approach; and 'sensitive areas' were identified by quantifying erosion potential and sediment transport. The work was supported by an assessment of free‐flowing rivers in Zambia, i.e., those rivers where aquatic ecosystem functions and services are largely unaffected by changes to fluvial connectivity through dams and other infrastructure. Highly ranked sub‐catchments were found in the Liuwa, Barotse, and Bangweulu floodplains and wetlands, and in the headwater regions of the upper Zambezi, Kafue, Chambeshi/Luapula, and Tanganyika catchments. The Luangwa was identified as the highest ranked candidate river for protection within Zambia. The resulting maps, data, and methods are intended to support national‐scale efforts to prioritize areas for surface water protection, identify catchments and rivers with high conservation value, optimize decision making for infrastructure development, and inform concerted strategies to maintain and restore freshwater ecosystem services in Zambia.